From Antithesis to Synthesis - Sutanto, Nathaniel Gray (Journal of reformed theology, 2015)
Recent scholarship further substantiates the observation that Cornelius Van Til depends on Herman Bavinck for his own constructive efforts. This observation creates a stimulus for comparative studies on the two theologians. In this essay I offer one such comparison by tracing an antithesis-synthesis strategy present in both Bavinck and Van Til. Though they share a motivation from the doctrine of common grace, the two theologians apply the strategy in distinct (though related) ways: Bavinck applies it for theological construction in a manner symbiotic with his organic ontology, while Van Til develops it into a self-consciously transcendental mode of reasoning and apologetics. This observation gives us insights as to why both theologians have been received (and misinterpreted) in similar ways, and that Van Til, though deeply dependent and influenced by Bavinck, developed Bavinck’s synthetic tendencies in ways that Bavinck did not do.